Translational research on Barrett's esophagus. (29th September 2014) - Baruah, Anushka; Buttar, Navtej; Chandra, Raghav; Chen, Xiaoxin; Clemons, Nicholas J.; Compare, Debora; El‐Rifai, Wael; Gu, Jian; Houchen, Courtney W.; Koh, Shze Yung; Li, Wenbo; Nardone, Gerardo; et al.
Abstract : The following, from the 12th OESO World Conference: Cancers of the Esophagus, includes commentaries on translational research on Barrett's esophagus that address evidence for genetic instability in esophageal cancer; the role of microsatellite instability; the use of histologic and serum Doublecortin‐like kinase 1 expression for progression of Barrett's esophagus to adenocarcinoma; the oxidative stress in Barrett's tumorigenesis; the genomic alterations in esophageal cancer; in vivo modeling in Barrett's esophagus; epigenetic and transcriptional regulation in Barrett's esophagus and esophageal adenocarcinoma; and normal and disordered regeneration in Barrett's esophagus.